2023
DOI: 10.1002/epi4.12785
|View full text |Cite
|
Sign up to set email alerts
|

Unfavorable public attitude toward people with epilepsy in Ethiopia: A systematic review and meta‐analysis study

Abstract: ObjectiveThis systematic review and meta‐analysis aims to show the pooled prevalence of unfavorable public attitude toward people with epilepsy (UPATPWE) as well as the effect estimates of associated factors in Ethiopia.MethodsBetween December 1 and 31, 2022, we searched for the English version of published research reports on public attitude toward epilepsy in Ethiopia in PubMed/Medline, Science Direct, Cochrane Library, Google Scholar, and PsycINFO. The research reports' quality was assessed using the Newcas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…In some studies conducted in the last decade, it has been observed that the belief that "Epilepsy is a mental illness, a mental health problem, caused by supernatural power, an infectious disease, occurs as a result of demon possession, and occurs as a result of the wrath of God" has been reported at very high rates (Table 1) [13][14][15][16][17][18][19][20][21][22][23][24]. There has been no serious positive development in knowledge and beliefs about epilepsy over time [25,26]. Regrettably, individuals with epilepsy often face negative attitudes and discrimination from others.…”
Section: Epilepsy and Stigmamentioning
confidence: 99%
“…In some studies conducted in the last decade, it has been observed that the belief that "Epilepsy is a mental illness, a mental health problem, caused by supernatural power, an infectious disease, occurs as a result of demon possession, and occurs as a result of the wrath of God" has been reported at very high rates (Table 1) [13][14][15][16][17][18][19][20][21][22][23][24]. There has been no serious positive development in knowledge and beliefs about epilepsy over time [25,26]. Regrettably, individuals with epilepsy often face negative attitudes and discrimination from others.…”
Section: Epilepsy and Stigmamentioning
confidence: 99%
“…The perception of epilepsy as a kind of insanity may increase the level of stigma. 21 , 22 , 23 , 24 , 25 , 26 , 27 …”
Section: Introductionmentioning
confidence: 99%
“…As a result of the belief that epilepsy is caused by evil spirits or demonic possessions, traditional medicine is appreciated over biomedicine for epilepsy treatment in sub‐Saharan Africa. The perception of epilepsy as a kind of insanity may increase the level of stigma 21–27 …”
Section: Introductionmentioning
confidence: 99%